FACTORS AFFECTING THE TERRITORIAL LOCATION AND DEVELOPMENT OF SERVICE NETWORKS (EXAMPLE OF TOG AND TOGOLDI DISTRICTS OF KASHKADARYA REGION) - Nasiba I. Safarova; Muhiddin Sh. Khidirov (International Scientific and Current Research Conferences, 2023)
Factors affecting the territorial location and development of service networks in Kashkadarya region: including the rapid growth of the population in the region in recent years, the establishment of new settlements, for the quality of life of residents in settlements far from the district centers the practical work on the development of service networks, ensuring the employment of the population has been highlighted.